Screening Indigenous Bodies. Issue 1 (1st June 2019) - Bergen-Aurand, Brian
Abstract : This issue acknowledges the work of Rosalie Fish (Cowlitz), Jordan Marie Daniels (Lakota), and the many others who refuse to ignore the situation that has allowed thousands of Indigenous women and girls to be murdered or go missing across North America without the full intervention of law enforcement and other local authorities. As Rosalie Fish said in an interview regarding her activism on missing and murdered Indigenous women and girls (MMIWG), "I felt a little heavy at first just wearing the paint. And I think that was . . . like my ancestors letting me know . . . you need to take this seriously: "What you're doing, you need to do well." And I think that's why I felt really heavy when I first put on my paint and when I tried to run with my paint at first. . . . I would say my personal strength comes from my grandmas, my mom, my great grandma, and I really hope that's true, that I made them proud." (Inland Northwest Native News interview)